Ayatollah Khomeini and the radicalization of Shiite ulama in the anti-shah movement in Iran - A. V. Baranov (Гуманитарные и юридические исследования)
The article analyzes the evolution of Ayatollah Khomeini’s political views on the reforms proposed by the Shah’s authorities, which became known as the «White Revolution». The reforms announced by the Shah split Ulam and the country into supporters and opponents of the Shah’s initiatives. Based on the study of sources, first of all, such as the collections of the works of Ayatollah Khomeini himself – «Kawthar» and «Sahifeh-ye Imam», the dynamics of Khomeini’s approach to the Shah’s initiatives, their criticism, and radicalization under the influence of the confrontational position of the Iranian authorities associated with the referendum in January 1963 are traced. The article attempts to correct the well-established approach in Russian historiography about the conservatism of Shiite Ulama and Khomeini’s views on such a controversial issue as women’s rights in Iran, which is emphasized by Khomeini’s opponents. However, after analyzing the Ayatollah’s speeches and statements, during his discussion with the country’s authorities, Khomeini focuses on the illegality and unconstitutionality of the shah’s reforms. Having failed to reach a compromise with the authorities, who resorted to forceful measures and the persecution of opponents, Khomeini, appealing to the religious memory of the Shiite tradition of the holy month of Muharram and the cult of Imam Hossein ibn Ali, called for an uprising and the overthrow of the shah’s power in Iran. The failure of the peaceful protest led to the radicalization of the opposition, which resulted in the bloody events of June 4-5, 1963. The subsequent arrest, and then the expulsion of Ayatollah Khomeini in November 1964 from the country, made him a staunch opponent of the monarchy, the leader of radical Shiite ulama and a supporter of building in Iran of the Islamic Republic.